Aero-hydro-elastic simulation of a semi-submersible floating wind turbine - Philippe, Maxime; Babarit, Aurélien; Ferrant, Pierre (Volume 7: Ocean Space Utilization; Ocean Renewable Energy, 2012)
ASME 2012 31st International Conference on Ocean, Offshore and Arctic EngineeringVolume 7: Ocean Space Utilization; Ocean Renewable EnergyRio de Janeiro, Brazil, July 1–6, 2012Conference Sponsors: Ocean, Offshore and Arctic Engineering DivisionISBN: 978-0-7918-4494-6 International audience This paper presents an aero-hydro-elastic model of a semisubmersible floating wind turbine. A specific attention is drawn to hydrodynamic modelling options and its effect on the dynamic response of the platform. The NREL 5MW reference wind turbine mounted on the historical concept of semi-submersible platform Dutch Tri-floateris considered. A specific hydrodynamic model of loads on semisubmersible platform is used within the wind turbine design code FAST from NREL. This hydrodynamic model includes non linear hydrostatic and Froude-Krylov forces, diffraction/radiation forces obtained from linear potential theory, and Morison forces to take into account viscous effects on the braces and damping plates. The effect of the different hydrodynamic modelling options is investigated. As one could have expected, it is found that the effect of viscous drag and non linear Froude-Krylov loads, becomes larger with increasing wave height. Simulations are run with directional wave spectrum, it is found that wave directionality induces larger transverse motions.